City Branding and Place Branding in the Metaverse: How Real Cities Build their Virtual Image and How Virtual Cities Do It - Sidorenko Bautista, Pavel (Fuori Luogo Journal of Sociology of Territory, Tourism, Technology, 2022)
Although the concept of the Metaverse dates back to the end of the 20th century and the first open platforms to the first decade of the 21st century with cases such as Second Life or Roblox, today it has gained much celebrity and transcended the media because of the structural changes of the now-defunct Facebook Corporation (now "Meta"), as well as Epic Games, parents of the popular Fortnite. It is worth mentioning that the remarkable evolution of connections, mobile technologies, and greater digital literacy on a global scale has made this type of initiative more relevant today. The technological field has expressed its intention to move towards the development of virtual spaces that serve as a social, productive, and recreational extension of individuals, considering three fundamental elements: interactivity, corporeality, and persistence. The initiatives are being very diverse, posing an important range of categories and options from closed environments, directly controlled by companies (as is the case today with the most popular social networks) to other decentralized and more open ones based on the block chain. Regardless of their quality or category, these metaverses propose, as they have been doing since the first decade of the 21st century, a privileged space for creativity and contact with new user segments, but, above all, for the evolution of dialogues in digital environments. Since the early days of Second Life, it has been possible to see how brands, companies, institutions, and professionals of all kinds have carried out projects in which they have not only transferred real-life experiences but have raised others natively in these virtual scenarios, thus reaffirming an innovative attitude. Like these actors, cities have expressed their intention to continue pushing and advancing in their public diplomacy processes by entering these platforms through functional replicas, where individuals not only relate to each other but can learn more about these cities, get in touch with them, with their services and heritage offer, in addition to offering activities and services native to the environment. However, there has also been the phenomenon of the construction and development of "cities" or "settlements" of the Metaverse, with very particular aesthetics and synergies, especially in decentralized proposals on block-chain systems such as Decentraland or The Sandbox. Thus, this research aims to study how the concepts of ’place branding’ and ’city branding’ are approached with a focus on the Metaverse and from the Metaverse itself: differences, similarities, particularities, determining elements, and projections. Through a comparative analysis, it will be possible to know how this incipient process is faced from the communication point of view, as well as a possible rethinking of the concept of the city. The results point to few experiences now, where in some cases the goal is to develop digital thematic extensions of strategic areas of real cities, while others are erected natively in this virtual scenario.